2012
DOI: 10.1136/bmjopen-2012-001032
|View full text |Cite
|
Sign up to set email alerts
|

A cost-utility analysis of transcatheter aortic valve implantation in Belgium: focusing on a well-defined and identifiable population

Abstract: BackgroundPatients with severe aortic stenosis and coexisting non-cardiac conditions may be at high risk for surgical replacement of the aortic valve or even be no candidates for surgery. In these patients, transcatheter aortic valve implantation (TAVI) is suggested as an alternative. Results of the PARTNER (Placement of AoRTic TraNscathetER Valve) trial comparing the clinical effectiveness of TAVI with surgical valve replacement and standard therapy were published. The authors assessed the cost-effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
104
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(111 citation statements)
references
References 13 publications
3
104
0
Order By: Relevance
“…These data are rarely presented and we consider the results to be of special relevance to economic modelling analyses set in Germany, where the various outcomes of our study may be used as inputs [2][3][4][5][6]22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are rarely presented and we consider the results to be of special relevance to economic modelling analyses set in Germany, where the various outcomes of our study may be used as inputs [2][3][4][5][6]22].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for the cost-effectiveness of TAVR generally agrees that TAVR is competitive compared to standard medical therapy, with multiple studies finding the cost-benefit ratio of TAVR to be within the acceptable range for the healthcare systems examined [2][3][4][5], with one notable exception from Belgium [6]. Comparisons of TAVR and SAVR have been less conclusive, possibly due at least in part to a lack of strong clinical data underpinning the analyses, since accurate published cost data for TAVR procedures is somewhat limited due to difficulties in collecting data from most systems [7].…”
Section: Introductionmentioning
confidence: 99%
“…126 TAVI was shown to be cost-effective when compared with conservative treatment in symptomatic patients who are not candidates for SAVR, [127][128][129][130][131][132] and it was even more cost-effective in the subgroup of anatomically inoperable than medically inoperable patients 133 and in those with a lower burden of noncardiac comorbidities. 134 Compared with SAVR in operable high surgical risk patients, evidence of cost-effectiveness of TAVI is much less consistent.…”
Section: Cost-effectiveness Issuesmentioning
confidence: 99%
“…Prior studies have reported incremental cost-effectiveness ratios ranging from £16 100 6 to $61 900 per QALY gained, 7 with intermediate values reported in the US dollars, 8 Canadian dollars, 9,10 and Euros. 11 Thus, the current study has reached a somewhat more pessimistic view of the cost-effectiveness of TAVR than a number of other independent analyses that were largely derived from the same data set.…”
Section: Article See P 419mentioning
confidence: 99%
“…TAVR may be a much better value for patients who are inoperable for technical reasons rather than because of severe, complex comorbidity 11 because the life expectancy gain in these relatively lower risk patients is greater. 3 Researchers will need to continue trying to define patient groups for whom TAVR is truly futile to better inform patients who are considering the procedure and to facilitate the decision making of heart teams.…”
Section: Reynolds and Cohenmentioning
confidence: 99%